Central Nervous System Complications of Erdheim-Chester Disease FDG PET/CT Findings - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Erdheim-Chester disease is an uncommon non-Langerhans cell histiocytosis. The diagnosis depends on imaging and histological criteria. The most common presentation is the multiple bone lesions with involvement of at least 1 more organ. We present the FDG PET/CT findings of a 19-year-old man who presented with central nervous system symptoms such as progressive polyuria, polydipsia, gait disturbances, and eye pain and was later diagnosed with Erdheim-Chester disease.
Keywords: Erdheim-Chester disease; FDG; PET/CT; non-Langerhans; eye; hypophysis; INVOLVEMENT; CT